Insight into biological strategies and main challenges to control the phytopathogenic bacterium Xylella fastidiosa - Mourou, Marwa; Incampo, Giuseppe; Carlucci, Mariangela; Salamone, Davide; Pollastro, Stefania; Faretra, Francesco; Nigro, Franco (Frontiers in Plant Science, 2025)
Xylella fastidiosa is a xylem-restricted bacterium that can infect a wide range of host plants. The European Union classifies Xylella fastidiosa as a quarantine pathogen. Since its initial outbreak in the Apulia region of southern Italy in 2013, it has caused a severe disease in Olea europaea, known as olive quick decline syndrome (OQDS). Alarmingly, X. fastidiosa has continued to spread and establish itself in several European countries, including Spain, France, and Portugal. In response, researchers have conducted numerous studies to identify effective strategies for limiting the spread of the bacterium and its primary insect vector, Philaenus spumarius L. These efforts have explored a wide range of approaches, including sustainable treatments, biological control agents, plant breeding techniques, and vector management strategies. This review aims to summarize the current research landscape and highlights the potential for improved management of this significant phytopathogen. The ongoing threat posed by X. fastidiosa underscores critical challenges for the future of agriculture in Europe and beyond. Furthermore, we identify key areas that remain poorly understood and require further investigation to develop effective and reliable control measures for this pathogen.